Environmental Management Practice and Environmental Performance: The Indirect Effect of Managers Attributes - Jamil, Che Zuriana Muhammad; Mohamed, Rapiah; Ariffin, Zaimah Zainol (International Review of Management and Marketing, 2017)
Activities related to environmental management practices (EMP) have been recently discussed in the hospitality industry. With the growth of the Tourism industry around the world, the new trends of tourism direct to Responsible Tourism and Meaningful Tourism which need “everything Green,” the practice of environmental management has been introduced. However, among the environmental issues discussed in the hospitality industry, the role of managers' attributes on environmental issues is rarely investigated. Therefore, this paper studies the role of manager attributes (MA) on the relationship between EMP and EP. A survey was administered to 350 managers from 4 and 5 star hotels, which were derived from Hotel Accommodation Booklet produced by Tourism Malaysia. The response rate was 11.7%. Partial least square was used to conduct the analysis. The study indicates that EMP has no contribution to the environmental performance, but the relationship turns significant when MA are considered as a moderator. Keywords: Environmental Management Practices, Environmental Performance, Manager Attributes JEL Classifications: M40, M41, M49